1976
DOI: 10.1128/aac.10.4.765
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Resistance to Proflavine and Penicillin in Escherichia coli

Abstract: A number of proflavine (PF)-resistant mutants ofEscherichia coli B were also resistant to penicillin and cephalothin. Mutants resistant to 1.0 mM PF were 10 times more penicillin resistant than were the PF-susceptible, wild-type cells. Single-step mutants selected for resistance to either PF or penicillin were also resistant to the other drug. None of the resistant mutants tested possessed /8-lactamase activity. These results suggest that resistance to PF and penicillin in E. coli B may be due to permeability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, Kushner and Khan (16) found no difference in the binding of proflavine to resistant and sensitive E. coli and showed that there is an active excretion system for the dye. However, a more recent study 'by McKeller et al (18) showed cross-resistance of proflavine and penicillin resistance in E. coli without any (3-lactamase activity, suggesting permeability changes in the cell envelope. A different approach, therefore, was made to study the involvement of the cell membrane in the AF resistance mutation.…”
Section: Resultsmentioning
confidence: 99%
“…However, Kushner and Khan (16) found no difference in the binding of proflavine to resistant and sensitive E. coli and showed that there is an active excretion system for the dye. However, a more recent study 'by McKeller et al (18) showed cross-resistance of proflavine and penicillin resistance in E. coli without any (3-lactamase activity, suggesting permeability changes in the cell envelope. A different approach, therefore, was made to study the involvement of the cell membrane in the AF resistance mutation.…”
Section: Resultsmentioning
confidence: 99%